1996
DOI: 10.1111/j.1751-0813.1996.tb09966.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of enzyme‐linked immunoassays for antibody to types C and D botulinum toxins for investigations of botulism in cattle

Abstract: The development of specific enzyme-linked immunosorbent assays (ELISA) for antibody to types C and D Clostridium botulinum toxins for investigation of botulism in cattle is described. Partially purified type C and D toxins were used as antigens to develop these ELISAs. Specificity of the ELISAs was evaluated on sera from 333 adult beef and dairy cattle from areas with no history or evidence of botulism in animals or water birds. The test was also evaluated on sera from 41 herds that included herds vaccinated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 13 publications
0
11
1
1
Order By: Relevance
“…Based on the above results, we concluded that the botulism toxoids can confer adequate protection against natural exposure to lethal doses of BoNT/D but that vaccination protocols used on dairy farms were inadequate and should be optimized. However, lower anti-BoNT/D IgG levels in younger animals might be explained by repeated natural exposure to subclinical toxin levels of older animals, as previously demonstrated in Australia (13). The results of our study differ from those of previously reported vaccination studies of cattle (15,34), which demonstrated better protection after fewer inoculations; this difference might be explained by exposure to higher levels of toxin or botulinum strain differences.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Based on the above results, we concluded that the botulism toxoids can confer adequate protection against natural exposure to lethal doses of BoNT/D but that vaccination protocols used on dairy farms were inadequate and should be optimized. However, lower anti-BoNT/D IgG levels in younger animals might be explained by repeated natural exposure to subclinical toxin levels of older animals, as previously demonstrated in Australia (13). The results of our study differ from those of previously reported vaccination studies of cattle (15,34), which demonstrated better protection after fewer inoculations; this difference might be explained by exposure to higher levels of toxin or botulinum strain differences.…”
Section: Discussioncontrasting
confidence: 57%
“…Two days thereafter, a group of pregnant heifers, the biggest and oldest of the VOL. 13,2006 PROTECTIVE LEVELS OF ANTI-BOTULINUM D ANTIBODIES 863 lot, which were in the last feeding group, were found either dead or recumbent (index cases). Within 5 days, 55 of 57 (96%) replacement heifers (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No entanto, pode-se deduzir que a ingestão contínua, mesmo de dose subletal, tenha como conseqüência o aumento da susceptibilidade dos animais a uma eventual intoxicação letal. Na realidade, o fato de bovinos criados extensivamente e não vacinados contra o botulismo apresentarem anticorpos contra as toxinas C e D (Gregory et al 1996) revela que este é um evento comum em áreas endêmicas.…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified